PERBAIKAN KUALITAS PRODUK OLAHAN UMKM SIRUP BUAH PARIJOTO BU SUTANTI GAMPING, SLEMAN - Widyasaputra, R.; Adisetya, E.; Firmansyah, R.; Sibarani, J.R. (Buletin Udayana Mengabdi, 2022)
Parijoto fruit has been a symbol of Sleman since 2014. This fruit contains high antioxidant which is good for health. Mrs. Sutanti has the small medium enterprise that focus on production of parijoto syrup. However, her product has the quality problem. This community partnership program aimed to improve the parijoto syrup quality and production process. This program was held through several stages. (1) Discussion and observation of the existing production process and formula; (2) Determination of new product formulation; (3) The implementation of new product formula. The experiment of new formula was held in 11-30 August 2021. This experiment resulted the new parijoto syrup formula (1:3 parijoto juice to water ratio, and 15% (g/g) of lime juice addition). This new formula had 65% of total dissolved solids. The implementation of this new product formula was held in 15 September 2021.   Keywords: formula, parijoto, production, quality, syrup.